Desain Interkoneksi Jaringan Menggunakan Vpn Internet Untuk Mendukung Sistem Pemerintahan Berbasis Elektronik - Yayan Candra Subidin; Darius Antoni (STMIK Budi Darma, 2022)
The rapid advance in information and communication technologies developement has greatly facilitated the development of electronic government worldwide. This can be seen from the various applications of information technology in government agencies, including integrated Electronic-Based Government System (SPBE). Numerous government agencies have implemented SPBE services for their daily operations. However, there are not infrequently the initiative for the existence of ICT infrastructure in several government institutions has some issues because due to various aims and backgrounds in developing it. The issues such, development of ICT network infrastructure is less efficient and effectiveness, the absence of a standard network system configuration, and the network security system underestimated. Therefore, this research will be designed and built ogan komering ulu regency government network systems using IPv4-based internet VPN with Network Development Life Cycle (NDLC) method. The purpose of this research is to provide a model of uniformity in the preparation of government network configurations, realize network interconnection between government agencies that make better utilization of network infrastructure, and support SPBE in Goverment of Ogan Komering Ulu District and improve aspects of network security in government. The results of this study indicate that by using a VPN network interconnection design, private network communication that passes through the public network (internet) will be more secure so that data confidentiality is maintained. The quality of data exchange in the form of images, sound, and text is better with a stable speed and maintained security. The use of IPv4 for network interconnection is used to reach all government agencies in the Scope of Government of Ogan Komering Ulu Regency.